2018
DOI: 10.1096/fj.201701205r
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous bioactive lipid prostaglandin D 2 ‐glycerol ester reduces murine colitis via DP1 and PPARγ receptors

Abstract: Cyclooxygenase-2 (COX-2) has long been implicated in the pathogenesis of inflammatory bowel diseases (IBDs). COX-2 is mostly known for the production of prostaglandins (PGs) from arachidonic acid. However, it also metabolizes the endocannabinoids 2-arachidonoylglycerol (2-AG) and anandamide into the less well-studied bioactive lipids PG-glycerol esters (PG-Gs) and PG-ethanolamides (PG-EAs or prostamides). We previously showed that PGD-G, a product of 2-AG oxygenation by COX-2, has anti-inflammatory effects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Such a relationship between endocannabinoids and PGs is also found between cannabinoids and PPAR agonists (Sun and Bennett, 2007). Thus, Alhouayek et al (2018) studied the effect of a bioactive prostaglandin derived from the oxygenation of 2-AG to PGD2-G by COX2 and a hematopoietic PGD synthase (PGDS). They reported the first dual activation of PGD2 receptor (DP1) and PPARg by PGD2-G and its anti-inflammatory properties in a murine model of colitis.…”
Section: Pparg Activation By Cox2 Products In Ulcerative Colitismentioning
confidence: 92%
“…Such a relationship between endocannabinoids and PGs is also found between cannabinoids and PPAR agonists (Sun and Bennett, 2007). Thus, Alhouayek et al (2018) studied the effect of a bioactive prostaglandin derived from the oxygenation of 2-AG to PGD2-G by COX2 and a hematopoietic PGD synthase (PGDS). They reported the first dual activation of PGD2 receptor (DP1) and PPARg by PGD2-G and its anti-inflammatory properties in a murine model of colitis.…”
Section: Pparg Activation By Cox2 Products In Ulcerative Colitismentioning
confidence: 92%
“…Sample analysis was based on previously described methods 12,26 . Briefly, we used a Xevo TQ‐S mass spectrometer (Waters) coupled to an Acquity UPLC class H (Waters) for sample analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Studies towards the biological activity of some of these other secondary ARA metabolites showed that PGD2-G, for example, has strong anti-inflammatory effects by reducing the formation of the proinflammatory cytokines in LPS administrated mice 100 , and by reducing DSS induced murine colitis 101 .…”
Section: Oxygenation Of Endocannabinoids: the First Evidence Of Oxygementioning
confidence: 99%